Research progress on antitumor effects of sea buckthorn, a traditional Chinese medicine homologous to food and medicine - Xu, Duojie; Yuan, Ling; Meng, Fandi; Lu, Doudou; Che, Mengying; Yang, Yating; Liu, Wenjing; Nan, Yi (Frontiers in Nutrition, 2024)
Sea buckthorn (Hippophae Fructus), as a homologous species of medicine and food, is widely used by Mongolians and Tibetans for its anti-tumor, antioxidant and liver-protecting properties. In this review, the excellent anti-tumor effect of sea buckthorn was first found through network pharmacology, and its active components such as isorhamnetin, quercetin, gallic acid and protocatechuic acid were found to have significant anti-tumor effects. The research progress and application prospect of sea buckthorn and its active components in anti-tumor types, mechanism of action, liver protection, anti-radiation and toxicology were reviewed, providing theoretical basis for the development of sea buckthorn products in the field of anti-tumor research and clinical application.